Phosphorus and Nitrogen Adsorption by Clinoptilolite Zeolite Coated with Iron-Oxide. Issue 20 (13th November 2019) - Sloan, John J.; Ampim, Peter A.Y.; Jaber, Fouad
ABSTRACT: Clinoptilolite zeolite coated with hydrous ferric oxide (FeZeo) may improve nutrient retention when blended into sand-based root zones. The objective of this study was to evaluate the effects of nutrient-charged FeZeo on nitrogen (N) and phosphorus (P) leaching and on growth of creeping bentgrass (Agrostis palustris Huds.). FeZeo was pre-loaded with 255 mg kg −1  N and 224 mg kg −1 P using a water-soluble fertilizer. Then, root zone mixes (RZM) containing 0, 5, 10, and 20% fertilizer-loaded FeZeo were packed into lysimeters and seeded with creeping bentgrass at a rate of 49 kg ha −1 . RZMs with 20% FeZeo received no additional fertilization whereas those containing 0, 5, and 10% FeZeo received four additional fertilizer applications during the next 8 months so that the cumulative N and P rates for every lysimeter were equivalent to 149 kg ha −1 and 131 kg ha −1, respectively. Lysimeters were irrigated every 2 to 3 days and leachate was collected and analyzed. Compared to putting green sand, the 5, 10 and 20% FeZeo treatments reduced the quantity of leached P by 96.2%, 91.3%, and 90.3%, and the quantity of leached N by 88.6%, 82.7% and 76.7%, respectively. Results suggest that pre-fertilized FeZeo applied to sand-based root zone mixes at 5 to 10% can significantly reduce nutrient leaching while maintaining acceptable plant growth, but higher rates of FeZeo can reduce plant growth. An alternative use for higher rates of FeZeo might include a filtering material for agricultural tile drainage. Abbreviations: cation exchange capacity (CEC), electrical conductivity (EC), iron-oxide coated clinoptilolite zeolite FeZeo, nitrogen (N), RZM, root zone mix